The journey of cardosin A in young Arabidopsis seedlings leads to evidence of a Golgi-independent pathway to the protein storage vacuole - Pereira, Cláudia; Vieira, Vanessa; Pissarra, José; Pereira, Susana (Frontiers in Plant Science, 2023)
The aspartic proteinase cardosin A is a vacuolar enzyme found to accumulate in protein storage and lytic vacuoles in the flowers and in protein bodies in the seeds of the native plant cardoon. Cardosin A was first isolated several decades ago and has been extensively characterised since, both in terms of distribution within the tissues and of enzyme biochemistry. In the native system, several roles have been addressed to cardosin A in reproduction, mobilization of reserves and membrane remodelling. To participate in such diverse events, cardosin A must accumulate and travel to different compartments inside the cell: protein storage vacuoles, lytic vacuoles, cytoplasmic membrane (and eventually outside the cell). Several studies have approached the expression of cardosin A in Arabidopsis thaliana and Nicotiana tabacum with promising results for the use of these systems in the study of cardosin A trafficking. A poly-sorting mechanism has been uncovered for this protein as two different vacuolar sorting determinants, mediating different vacuolar routes, have been described. The first is a conventional C-terminal domain, which delivers the protein to the vacuole via Golgi, and the second, an unconventional signal – Plant Specific Insert (PSI) – that mediates a Golgi-independent route. The hypothesis that these two signals are activated according to cell needs and in organs with high metabolic activity is here investigated. An Arabidopsis line expressing cardosin A under an inducible promoter was used to understand cardosin A dynamics regarding vacuolar accumulation during seed germination events. Using antibodies against different regions of the protein and combining them with immunofluorescence and immunocytochemistry assays in different young seedlings tissues cardosin A was detected along the secretory pathway to the Protein Storage Vacuole, often associated with the endoplasmic reticulum. More interestingly, upon treatment with the drug Brefeldin A, cardosin A was still detected in protein storage vacuoles indicating that the intact protein can bypass the Golgi in this system, contrarily to what was observed in N. tabacum. This study is a good starting point to further research involving the use of fluorescent fusions and exploring in more detail the relationship between cardosin A trafficking and plant development.